Green Human Resource Management in Supporting Environmentally Friendly Behavior - Sutarto Hadi; Ismi Rajiani; Mutiani Mutiani; Nur Laily As Syifa; Akhmad Hapis Ansari; M. Ridha Ilhami (The Innovation of Social Studies Journal, 2023)
This article aims to describe Green human resource management (GHRM) as an effort to support environmentally friendly behaviour. GHRM must be explained conceptually so that green human resource management practices can be well understood. This article was prepared using the library study method. Performance management in the management environment provides a challenge in measuring environmental performance standards in various corporate units and obtaining useful data for managers about environmental performance. Green performance appraisal includes themes such as environmental responsibility, environmental incidents and knowledge of environmental policies and issues, as the issues involved in environmental performance appraisal relate to the requirement for managers to be held accountable for environmental performance. Green performance appraisal is a process in which employees are stimulated to enhance professional skills in environmental issues, which helps to achieve environmental performance goals and objectives in a better way. The green reward system plays an important role in motivating people and helping to identify their significant performance towards environmental stewardship.